Skill Improvement for Vocational High School Graduates through Hybrid Learning: A Case Study of SMK Negeri 7 Bandung - Ermawati, Ermawati; Iim Wasliman; Nandang Koswara; Ahmad Khori (CV. Media Digital Publikasi Indonesia, 2026)
Vocational education in Indonesia faces the challenge of ensuring that graduates have the skills that match industry requirements. The hybrid learning model, which combines online and face-to-face methods, is increasingly being adopted as a strategy to improve the quality of graduates’ learning. This investigation examines the efficacy of hybrid learning in enhancing students' technical and interpersonal competencies, while also exploring their perceptions of this educational model at SMK Negeri 7 Bandung. This study used a mixed-methods approach, with quantitative data collected through surveys and pre- and post-intervention assessments, and qualitative data obtained through interviews and classroom observations. The sample consisted of students enrolled in various vocational programs, and the data were analyzed using descriptive statistics and thematic analysis. Hybrid learning contributed to a 25% improvement in technical skills and a 30% improvement in soft skills (communication, teamwork, and problem-solving). A total of 85% of students expressed satisfaction with this model, with flexibility and accessibility being the main factors. However, some students faced challenges in adapting to technology. Hybrid learning is effective in improving the skills and job readiness of vocational high school students, but its implementation requires support in the form of technology training and curriculum adjustment.